DNA damage and oxidative stress in gill cells of Cnesterodon decemmaculatus exposed to pesticides by runoff source in an agricultural basin - Pautasso, Nestor Abel (2023)
In our country, great concern exists about diffuse pollution cause by the great use of pesticides in rural environments. A thorough analysis is needed to generate information, know the real situation and thus, be able to make decisions with the purpose of reducing environmental pollution. In situ bioassays have been carried out using Cnesterodon decemmaculatus within limnocorrals located in a surface natural water system that receive rainfall excess flowing from an agricultural basin with a typical crop rotation, including corn, wheat and soy. Specimens were taken from the limnocorrals 72 h after a probed natural runoff event towards the water body, and the gill cells were used to evaluate the DNA damage (comet assay, CA), catalase enzyme activity (CAT) and lipid peroxidation (LPO). In addition, the physicochemical analysis of the water (pH, temperature) and the presence and concentration of pesticides were carried out. The results showed significant differences on DNA damage and oxidative stress on the gill cells of the exposed fish compared to controls, being the combination of the rain regime and the mixtures of pesticides used in corn and soy more toxic than in wheat. These results highlight the necessity to understand detrimental processes caused by pesticides used in extensive systems of primary production, in order to prevent and minimize diffuse contamination, contributing to environmental recovery and sustainability.